The ordination of Catholic women as deacons: The state of the question - Rakoczy, Susan (HTS teologiese studies, 2020)
The report of a commission set up by Pope Francis to study the question of women as deacons in the Catholic Church was issued in May 2019. Whilst it is well known that the Catholic Church refuses to ordain women, the form of the diaconate being discussed is that of the ‘permanent diaconate’ for men, which was established after the Second Vatican Council (1962–1965). This article first discusses how this issue has arisen, clarifies the types of deacons and reviews the reasons why the Catholic Church refuses to ordain women. It then looks at Scripture and the history of the Church to assess the historical role of women deacons. The issue of women’s ordination emerged after Vatican II (1962–1965). Women’s ministries have grown immensely since then and this is a factor in the question about the ordination of women deacons. There are important theological issues involved in the study around women deacons. Lastly, the article raises questions about the future of this issue under Pope Francis and his successors.Contribution: The issue of the ordination of women deacons in the Roman Catholic Church is a current and contentious issue. This article reviews the historical evidence for women deacons and the views of theologians and Church leaders in order to assess whether there are grounds for hope.